OPPORTUNITIES FOR SUSTAINABLE FOREST MANAGEMENT IN YUNDOLA - Paligorov, Ivan; Galev, Emil; Kovacheva, Stanislava; Dragozova, Elena; Ivanov, Ivaylo (Innovation in Woodworking Industry and Engineering design, 2017)
The forest management in Yundola has been studied under the project INTEGRAL - Future-Oriented Integrated Management of European Forest Landscapes by the funding Scheme: FP7 Seventh Framework Programme. This is one of the project case study areas in Europe. This is one of the objects of a test project in Europe. The results of the survey are the bases of the development of future scenarios for forest management and they make it possible to create the integrated management strategies for sustainable use of forest landscapes. The supply of all forest ecosystem goods and services is expected to increase in all case studies in the future. This causes an emerging need for a pro-active management approaches to handle trade-offs and strike a balance in order to address sustainability concerns in building the bio-based economy.